Gambaran Sel Eosinofil, Monosit, dan Basofil Setelah Pemberian Spirulina pada Ayam yang Diinfeksi Virus Flu Burung (OBSERVATION OF EOSINOPHILS, MONOCYTES, AND BASOPHILS AFTER TREATED WITH SPIRULINA IN CHICKENS THAT INFECTED WITH AVIAN INFLUENZA VIRUS) - Lokapirnasari, Widya Paramita; Yulianto, Andreas Berny (Jurnal Veteriner; Vol 15 No 4 (2014), 2015)
High Pathogenecity Avian Influenza (HPAI) viruses have high virulence and can frequently causesudden death on birds. The aims of this research was to know the role of Spirulina to a number ofmonocytes and lymphocytes in the blood of chickens which infected with the H5N1 virus. This researchconsisted of three levels of treatment in which each level given Spirulina 0%, 10%, 20% in the fresh wateralgae as drinking water. Each treatment consisted of seven replicates, and the treatment was done sincethe chickens at age 19 until 44 days ( for 25 days). Artificial infection of the chickens with the virus waschallenged by using AI (H5N1) 104 EID 50 (A/Ck/Indonesia/BL/03) with route to the respiratory tract (nosedrops) 0,1 mL starting on day 19. The results showed that there were a significant difference (p<0.05) ontreatment that given Spirulina at doses of 0%, 10% and 20% for the number ofn monocytes, eosinophils,whereas no significant difference (p > 0.05) was observed in basophils.
Keywords: chicken, Spirulina, H5N1 virus, monocytes, eosinophils, basophils